Association of ABCB1 C3435T polymorphism with the susceptibility to osteonecrosis of the femoral head: A meta-analysis. Issue 20 (May 2017) - Zhang, Yu; Xie, Hui; Zhao, Dewei; Wang, Benjie; Yang, Lei; Meng, Qingyu
Abstract: Background and objective: The exploration for the etiology of osteonecrosis of the femoral head (ONFH) has got some promising findings, but the morbidity of ONFH is still not under control. The C3435T polymorphism of ATP-binding cassette subfamily B member 1 ( ABCB1 ) gene has been reported to possess significant influence on ONFH onset, but relevant outcomes remain conflicting rather than conclusive. Therefore, a meta-analysis was useful to pool these results together for a more reliable conclusion. Methods: The association of ABCB1 C3435T polymorphism with ONFH susceptibility was estimated through calculated odds ratios (ORs) with their 95% confidence intervals (95% CIs). The Q -test was applied for detecting inter-study heterogeneity, whereas sensitivity analysis for identifying any study owning substantial influence on pooled results. Begg's funnel plot and Egger's test were employed to examine publication bias across included studies. Results: ABCB1 C3435T polymorphism significantly decreased the risk of ONFH under TT vs CC (OR = 0.26, 95% CI = 0.13–0.50), TT+CT vs CC (OR = 0.72, 95% CI = 0.52–0.99), TT vs CC+CT (OR = 0.28, 95% CI = 0.15–0.52), and T vs C (OR = 0.64, 95% CI = 0.50–0.81) contrasts. Conclusion: The variant C3435T in the ABCB1 gene may offer protection against the attack of ONFH, and more studies with larger sample sizes should be conducted to certify this issue.